From Service Quality to Brand Loyalty: The Mediating Effect of Student Satisfaction in Public Sector Universities - Rahman, Atteeq ur; Manzoor, Waqas; Yasmin, Nazia; Yaqub, Rana Muhammad Shahid; Ali, Malik Sajid (Pakistan Journal of Humanities and Social Sciences, 2024)
Consumers and brands are crucial concepts and compelling research areas in brand management. A decade ago, researchers have noted that the brand equity’s concept is less explored in the education sector. Education system is too vital industries that are playing a major role in the society and growth of nation, thus highlighting its importance. Corporate industries prioritize customer satisfaction and loyalty, and some studies suggest that students should be considered customers. Consequently, universities need to enhance their understanding of brand equity-related concepts such as brand strength, brand image, and service quality. Providing high levels of service quality and cultivating a strong brand image leads to loyal customers. This study examines the mediating effect of student satisfaction on the relationships between brand strength, brand image, service quality, and loyalty. Using convenience sampling, we distributed 600 questionnaires to respondents from public sector universities in Pakistan. Service quality is identified as a multidimensional construct comprising interactional quality, outcome quality, and physical environment quality. These types are positively and significantly related to student loyalty. The study reveals that brand image and service quality show full mediation, while brand strength shows partial mediation. The results indicate that universities with a better understanding of their students, and those that share their plans and information effectively have more satisfied students. The findings regarding brand image suggest that universities should have a clear and definite vision to satisfy their students. Additionally, satisfied students feel honored to study at these institutions. Regarding service quality, the study suggests that universities with courteous, sympathetic, reassuring, and job-oriented administrative staff have more satisfied students. The perceived quality of the environment indicates that poor physical layouts, inadequate computer lab equipment, and insufficient campus facilities lead to student dissatisfaction. Furthermore, the results provide insights that can help university administrations develop strategies to enhance student satisfaction and retention. Current research paper contributes to the knowing of how universities can build and maintain brand loyalty by paying attention on mediating role of student’s satisfaction.